MANUSCRIPT HERITAGE AT THE COLLECTION OF KLAIPĖDA UNIVERSITY LIBRARY - ČESNULEVIČIŪTĖ, DANUTĖ; STEPONAVIČIŪTĖ, DANUTĖ (Knygotyra, 2012)
This paper presents a collection of manuscript heritage which is kept at the Department of Rare Books, Collections and Manuscripts of the Klaipeda University Library. At present, a total of 8 funds are already formed there. They are: Ansas Lymantas (f. 1), Kazys Pemkus (f. 2). Vilius Pėteraitis (f. 3), Ieva Jankutė (f. 5), Vytautas Strolia (f. 8), and others: score manuscripts (f. 4), single documents (f. 7), musicians in exile (f. 6). The collections of A. Lymantas (f. 1) and K. Pemkus (f. 2) could be regarded as the best analyzed ones. The content of the personal archives (K. Pemkus collection, f. 2), heritage of manuscripts in the archives of Lithuania Minor and the briefly described material placed in other collections and funds of the Department are reviewed in the paper. There are several groups of archives in the collection of K. Pemkus (a well-known bibliophile and therapist in exile): manuscripts of writers and linguists; historians; therapists; pedagogues; lawyers; artists; public figures; priests, etc. There are presented original texts (manuscripts and typescripts), corrections of texts, translations, notes, original letters or their copies, iconography, scraps about their creative work, personalities, programs of literary events, invitations and other small printings. The fund (f. 2) of Ansas Lymantas (representative of the press, journalist, a former citizen of Klaipėda), containing documents of organizations of Lithuania Minor in exile, materials of the „Lietuvos pajūris“ newspaper, biographical and public work documents is reviewed in more detail. The content of such funds as these of Vilius Pėteraitis (a public figure, lexicologist, KU doctor of Honour), Ieva Jankutė (a granddaughter of the well-known “Aušra” publisher Martynas Jankus), musician Vytautas Strolia, score manuscripts, musicians in exile, and the fund of single documents are briefly described. Information about this heritage could be found at the web site of the Department of Rare Books, Collections and Manuscripts at the Klaipeda University Library’s home page: http://www.ku.lt/libr/structure/retu.php